Perancangan Sistem Informasi Ekstrakurikuler Berbasis Web Pada SMPN 8 Sutera Pesisir Selatan - Jusmita Weriza; Wahyuni Yahyan; Tesa Junianti (Jurnal Sains Informatika Terapan, 2025)
Extracurricular activities at SMPN 8 Sutera do not yet have a system, resulting in frequent errors in the process of recording student registration data and extracurricular activities managed by the instructors. The objective of this final project is to design a web-based extracurricular application at SMPN 8 Sutera Pesisir Selatan that can facilitate students and instructors in the extracurricular activities process. The application design process uses the SDLC research method with the waterfall model, consisting of analysis, design, implementation, and testing. The design tools used are UML, consisting of use cases, class diagrams, activity diagrams, and sequence diagrams. The programming language used is PHP for server-side development, and MySQL serves as a database for storing extracurricular information. The result of this design is a web-based extracurricular system at SMPN 8 Sutera Pesisir Selatan.